2023
DOI: 10.1038/s41598-023-38146-1
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated reconstruction of rat calvaria bone defect using 3D-printed scaffolds coated with hydroxyapatite/bioglass

Abstract: Self-healing and autologous bone graft of calvaraial defects can be challenging. Therefore, the fabrication of scaffolds for its rapid and effective repair is a promising field of research. This paper provided a comparative study on the ability of Three-dimensional (3D) printed polycaprolactone (PCL) scaffolds and PCL-modified with the hydroxyapatite (HA) and bioglasses (BG) bioceramics scaffolds in newly bone formed in calvaria defect area. The studied 3D-printed PCL scaffolds were fabricated by fused deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…This approach enabled the sequential imaging of the rabbit specimens, allowing for the observation of structural changes at different time points. These sequential scans provided a comprehensive assessment of the evolving changes within the calvarial regions of the specimens over the designated time intervals [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…This approach enabled the sequential imaging of the rabbit specimens, allowing for the observation of structural changes at different time points. These sequential scans provided a comprehensive assessment of the evolving changes within the calvarial regions of the specimens over the designated time intervals [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Fazeli et al reported the deposition of HAp and BG onto 3D printed PCL scaffolds via an immersion method with a HAp/BG solution. 78 Zhang et al reported PCL scaffolds coated with HAp via pulsed laser deposition (PLD). 79 Li et al described HAp deposition onto PVA/PLA scaffolds via electrodeposition.…”
Section: Imparting Bioactivity To Scaffoldsmentioning
confidence: 99%